The caveman's valentine [large type] - Green, George Dawes (Compass Large Print, 1996)
A homeless man who spends his days waging a one-man war against the imaginary person he holds responsible for all of society's ills decides to find the person who murdered someone and left the body at the entrance to the cave he calls home.